"OPEN BALKANS" INITIATIVE PATH FROM IDEA TO SUSTAINABLE DEVELOPMENT (Heritage, 2024)
Throughout history, the fate of the countries of the Western Balkans was mainly determined by political factors, and their inclusion in the integration processes represents an attempt to give primacy to economic factors and sustainable development, in relation to political factors. Today, we encounter a large number of comments, statements by experts and representatives of political organizations about the potential effects of the "Open Balkans" initiative, but also the lack of serious theoretical and empirical research on its progress and potential effects on the sustainable development of the region. Precisely because of the above, the authors of this paper devote their attention to finding an answer to the question of how this initiative developed and what are its potential effects on sustainable development, i.e. to what extent it contributes to increasing the well-being of the members and neighboring countries. Empirical evidence for the acceptability of the most important views and conclusions presented in the paper was provided through research in which the first author of this paper participated, and based on data collected by the Faktor Plus Agency in all countries that signed the initiative.
Keywords: Integrations, common market, regional cooperation, sustainable development, freedom of movement